Critical Posthuman Nursing Care - Jane Hopkins Walsh; Jessica Dillard-Wright; Brandon Blaine Brown; Jamie Smith; Eva Willis (York University Libraries, 2022)
Nursing care is an embodied and co-creative world-building practice made hypervisible in pandemic times. A traditional praxis that became a professionalized care practice, nursing bares the indelible mark of the ideologies that have come to shape the discipline like whiteness, patriarchy, and capitalism to name a few. Embracing a critical feminist posthuman and new materialist perspective, in this paper we advance the notion that nursing care is a situated and embodied endeavor that cannot and should not be disconnected from sites of care, people receiving care, and the powers that structure care relations. Even in idealised contexts, nursing care is shaped by the confines of these forces. We tease out ideas that have molded nursing across time and within the epoch of the Covid pandemic. We draw upon imaginations from Arundhati Roy that the pandemic is a portal, an opportunity for rebirth. Care practices are proposed with a critical posthuman perspective, in the spirit of Haraway's idea of composting. Composting is used metaphorically as actions to morph and decay the boundaries beyond traditional notions of care based in humanism. We imagine this in an effort to rethink what worlds we want to co-produce, a call to action where care can be revisioned as an arena where nurses, people, all matter, all creatures and worlds are co-created.